2020
DOI: 10.1038/s41420-020-00298-8
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effects of IL-17 and Astragaloside IV on cortical neurogenesis and cognitive behavior after stroke in adult mice through Akt/GSK-3β pathway

Abstract: We aimed to investigate the exact effect of IL-17 on regulating neural stem cells (NSCs) stemness and adult neurogenesis in ischemic cortex after stroke, how Astragaloside IV(As-IV) regulated IL-17 expression and the underlying mechanism. Photochemical brain ischemia model was established and IL-17 protein expression was observed at different time after stroke in WT mice. At 3 days after stroke, when IL-17 expression peaked, IL-17 knock out (KO) mice were used to observe cell proliferation and neurogenesis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 69 publications
2
16
0
Order By: Relevance
“…Indeed, previous studies have demonstrated the inhibitory effect of IL-17 on neurogenesis, in particular, on neural progenitor proliferation in vivo and in vitro [23,34,[42][43][44][45].…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, previous studies have demonstrated the inhibitory effect of IL-17 on neurogenesis, in particular, on neural progenitor proliferation in vivo and in vitro [23,34,[42][43][44][45].…”
Section: Discussionmentioning
confidence: 97%
“…In addition to its potential role in regulating the immune response to balance cytotoxic and tolerant immune profiles, it also results in acute injury. As a proinflammatory cytokine, IL-17 essentially incorporates a complicated network of cytokines that is responsible for various inflammatory conditions and pathogenesis (11)(12)(13)(14). The inflammatory response and cytokine production are particularly crucial in the progression of AP.…”
Section: Introductionmentioning
confidence: 99%
“…Knockout of IL-17 helps to regulate the PI3K-Akt pathway, promotes the proliferation of NSCs, and promotes nerve growth after IS. [ 22 ] This study found that the RPR-FC has neuroprotective effects, promoting nerve repair, vascular remodeling, inhibition of neuronal apoptosis, and regulation of inflammatory factor expression after IS.…”
Section: Resultsmentioning
confidence: 99%